2008
DOI: 10.1186/1471-2105-9-s12-s12
|View full text |Cite
|
Sign up to set email alerts
|

Real value prediction of protein solvent accessibility using enhanced PSSM features

Abstract: Background: Prediction of protein solvent accessibility, also called accessible surface area (ASA) prediction, is an important step for tertiary structure prediction directly from one-dimensional sequences. Traditionally, predicting solvent accessibility is regarded as either a two-(exposed or buried) or three-state (exposed, intermediate or buried) classification problem. However, the states of solvent accessibility are not well-defined in real protein structures. Thus, a number of methods have been developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
0
30
1
Order By: Relevance
“…The estimated accuracy of sequence-based RLA prediction is lower compared to RSA prediction in soluble proteins, with PCC between predicted and observed values of about 0.5 for RLA, as opposed to about 0.6-0.7 PCC for state-of-the-art RSA prediction methods [29,[32][33][34]. However, we demonstrated on several different sets of decoys that by comparing predicted and observed RLAs one can largely discriminate native and native-like from misfolded structures.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The estimated accuracy of sequence-based RLA prediction is lower compared to RSA prediction in soluble proteins, with PCC between predicted and observed values of about 0.5 for RLA, as opposed to about 0.6-0.7 PCC for state-of-the-art RSA prediction methods [29,[32][33][34]. However, we demonstrated on several different sets of decoys that by comparing predicted and observed RLAs one can largely discriminate native and native-like from misfolded structures.…”
Section: Discussioncontrasting
confidence: 52%
“…In this work, we focused on the relative lipid accessibility (RLA), which is a direct extension of the relative solvent accessibility notion used in the case of soluble proteins to characterize (in relative terms) the level of surface exposure for individual amino acid residues. Over the last two decades, many statistical and machine learning-based methods have been developed for the prediction of solvent accessibility in soluble proteins [26][27][28][29][30][31][32][33][34]. Recently, several methods have been proposed that extend these efforts to the prediction of lipid accessibility in alpha-helical transmembrane (TM) proteins, extrapolating from a limited, but steadily growing number of experimentally resolved structures [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The ASA values were computed based on the oligomeric states provided by OPM using DSSP with a probe radius of 1.4 Å 27 as with previous studies. 15,17,31,32 No further exploration on probe sizes was conducted because it has been shown that probe size has little or no effect on the performance of RSA predictors. 23 The ASA value of each amino acid type in an extended tripeptide conformation was adopted from a similar study.…”
Section: Methodsmentioning
confidence: 99%
“…[17], there are 84 sequences in the training dataset that was randomly selected, named the Sma dataset, for feature selection. Every protein was divided into a number of small segments using a sliding window 11 amino acid residues long [17], where the central residue of the segment is the prediction target while the five nearest bilateral residues provide additional information. All the segments were grouped according to their central residues, and 20 RSA prediction models were built.…”
Section: Methodsmentioning
confidence: 99%
“…Each residue of a segment was represented by a 21-dimensional vector that contains 20 values representing effective frequencies of occurrence at respective positions in a multiple alignment and an extra value for the terminal flag as described in the article by Chang et al . [17]. Finally, the PSSM of a segment was represented by 231 values.…”
Section: Methodsmentioning
confidence: 99%